Judging measurement fraud: a comparative look at Masoretic, Septuagint, ancient Near Eastern, and ancient Greek texts - Hopf, Matthias (Semitica et Classica, 2024)
Abstract Biblical law addresses the issue of false measuring devices and represents YHWH as the guardian of weights and measures. Surprisingly, however, the respective provisions in Lv 19 and Dt 25:13-16 do not explicitly mention any sanctions that such misdeeds would entail. Something very similar can be said about prophetic comments on this issue. This paper addresses this peculiarity in two ways: 1/ It presents a close philological analysis of the Masoretic Text and the Septuagint versions; and 2/ It takes a comparative approach, making use of other sources for ancient Near Eastern and ancient Greek law, to identify commonalities and differences with these neighboring cultures. The results show that the handling of the issue is not always strictly “legal” in nature but rather seems to fall in a gray area at the fringes of law and ethos. Moreover, measures and weights are dependent on standardization, which corresponds to the observation that more recent texts (especially the Septuagint) display greater interest in the legal regulation of this area. Finally, the fact that the Hebrew Bible remains silent on the legal consequences of fraud can be interpreted as a hint to the largely oral nature of everyday law in Israel at least until the Hellenistic period. Abstract La loi biblique aborde la question des faux instruments de mesure et présente YHWH comme le gardien des poids et mesures. Il est toutefois surprenant de constater que les dispositions respectives de Lv 19 et de Dt 25,13-16 ne mentionnent pas explicitement les sanctions que de tels méfaits entraîneraient. On peut dire la même chose des commentaires prophétiques sur ce sujet. Cet article aborde cette particularité de deux manières. 1/ Il présente une analyse philologique approfondie du texte massorétique et de la Septante. 2/ Il adopte une approche comparative, en prenant en compte les textes juridiques du Proche-Orient ancien et de la Grèce ancienne, afin d’identifier les points communs et les différences avec ces cultures voisines. Il en ressort que le traitement de la fraude en ce domaine n’est pas toujours de nature strictement « juridique », mais semble plutôt se situer dans une zone grise, à la limite du droit et de l’ethos. En outre, dans la mesure où les poids et mesures dépendent de la standardisation, les textes plus récents (en particulier la Septante) manifestent davantage d’intérêt pour la réglementation juridique dans ce domaine. Enfin, le fait que la Bible hébraïque reste silencieuse sur les conséquences juridiques de la fraude peut être interprété comme un indice de la nature largement orale du droit quotidien au moins jusqu’à l’époque hellénistique.